Analisis pola distribusi logam berat timbal serta pengaruhnya terhadap kualitas air di sepanjang Sungai Jeneberang Kabupaten Gowa - Patang Patang; Harifuddin Harifuddin; Andi Puspa Sari Idris (Seminar Nasional LP2M UNM, 2019)
The research aimed to determine the distribution of Lead (Pb) heavy metals in water, sediment and fish along the Jeneberang River. The research was conducted for 9 months, namely April to November 2018. The observation station consisted of 5 points, namely the Upper Jeneberang River, Bili-Bili Dam, Gowa Regency Twin Bridge, Jeneberang River Estuary and Losari Beach. Water sampling is carried out directly at each station that has been determined which is then analyzed in the laboratory. Supporting parameters which are secondary data include, measurement of temperature, dissolved oxygen, and pH carried out directly at the research station. Fish sampling is carried out on each station 2 times for 5 locations / stations. Sediment samples were taken using paralon pipes at a depth of approximately 20 cm, which were inserted into the sediments at each sampling station. To find out the condition of Pb lead heavy metal, data analysis is presented in the form of images and graphics. The results showed that the condition of the waters along the Jeneberang River associated with lead pollution is already on the verge of dangerous boundaries, but water quality such as temperature, pH and dissolved oxygen are still classified according to the needs of aquatic organisms. At all observation stations found several types of plankton, both phytoplankton and zooplankton, but the presence of plankton was not evenly distributed for all stations where phytoplankton and zooplankton species were found at all stations but other types were not found at certain stations.